New Ideas Concerning Black Holes and the Universe - Tatum, Eugene (IntechOpen, 2020)
The ideas presented in this book are new scientific theories based largely upon a spate of very recent astronomical observations. These theories include: a cosmological model that appears to be superior, in many respects, to the inflationary "concordance model"; proposed thermal stability criteria for a generic quantum black hole; theoretical constraints concerning black hole binary graviton emissions; theoretical effects of abelian vortices on space-time; and a proposed solution to the mystery of the observed asymmetry between universal matter and antimatter. The new ideas presented in this book have been selected in order to inspire others that, regardless of the impending limits of observation, the scientific creative process will continue.